Working time preferences, hours mismatch and well-being of couples: Are there spillovers? - Christoph Wunder; Guido Heineck (Bamberg University, Bamberg Economic Research Group (BERG), 2012)
We analyze how well-being is related to working time preferences and hours mismatch. Selfreported measures of life satisfaction are used as an empirical approximation of true wellbeing. Our results indicate that well-being is generally lower among workers with working time mismatch. Particularly underemployment is detrimental for well-being. We further provide first evidence on spillovers from the partner's working time mismatch. However, the spillover becomes insignificant once we control for the partner's well-being. This suggests that well-being is contagious, and the spillover is due to interdependent utilities. Females experience the highest well-being when their partner is working full-time hours. Male wellbeing is unaffected over a wide interval of the partner's working hours.
Keywords: I31; J21; J22; 330; subjective well-being; life satisfaction; working time preferences; working time mismatch; spillovers; utility interdependence